The Effect of Competency and Motivation on the Effectiveness of Goods Services Procurement with the Implementation of the Board of Directors Regulation of PT PLN (Persero) Number 0018.P/Dir/2023 as an Intervening Variable for Employees of PT PLN (Persero) UID North Sumatera - Eka Wiyono; Kiki Farida Ferine; M. Isa Indrawan (CV. Doki Course and Training, 2026)
This study aims to examine how Competence and Motivation influence the Effectiveness of Goods/Services Procurement, with the Implimentation of The Board of Direntors Regulation no. 0018.P/DIR/2023 as an intermediary factor among employees at the UID Office of PT PLN (Persero) North Sumatra. A total of 120 employees were selected through purposive sampling. Data analysis used Partial Least Squares (PLS) to evaluate the validity, reliability, and direct and indirect impacts between variables. The results showed that Competence and Motivation have a positive and significant effect on the Effectiveness of Goods/Services Procurement, both directly and indirectly through Direntors Regulation no. 0018.P/DIR/2023 implementation Direntors Regulation no. 0018.P/DIR/2023 implementation has been confirmed as a mediating factor that improves the relationship between Competence, Motivation, and Procurement Effectiveness. These results highlight the importance of improving competence, motivation, and the use of the E-Procurement system to improve procurement performance at PT PLN (Persero).